SEISMIC PROPERTIES OF THE INNER CORE BOUNDARY FROM PKIKP/P AMPLITUDE RATIOS - Koper K.D.; Dombrovskaya M. (My University, 2005)
A recent study of PKiKP / PcP amplitude ratios found surprisingly low values for the change in density (ΔρICB = 0.3 g/cm3) and shear velocity (ΔSICB = 2.0 km/s) across the inner core boundary (ICB). However, because the data set was limited to small source–receiver distances (< 50°) there was a significant trade-off between the two parameters, with higher values in one parameter nearly compensated by higher values in the other. In this study we augment the existing PKiKP/PcP data set with new observations of PKiKP / P amplitude ratios at larger distances (50–90°), and jointly model the two data sets. Considering assumptions in the modeling and observational errors we estimate ΔρICB = 0.52 ± 0.24 g/cm3 and ΔSICB = 2.82 ± 0.32 km/s. These values can be reconciled with the slightly higher values obtained from normal mode analysis if the outermost inner core is either structurally or chemically distinct from the bulk of the inner core. The new PKiKP / P amplitude ratios show dramatic variation but are geographically coherent; this suggests that significant lateral heterogeneity is present at, or just below, the ICB.
Keywords: inner core boundary; PKiKP; Seismic array